2019
DOI: 10.5541/ijot.570540
|View full text |Cite
|
Sign up to set email alerts
|

4E Analysis of Integrated MHD-Combined Cycle

Abstract: In recent years, there have been increasing studies on topping cycles of combined cycle power plants with very high working temperature (about 3000 K). One of the thermal cycles, which have the ability to work in this temperature range, is MHD-Magneto hydrodynamic-cycle. MHD cycle can operate in two states. One state is the open cycle, and the other one is the close cycle. In both mentioned states there is a large amount of waste heat that can be recovered. It seems that the use of recovered heat from MHD cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Exergy rates corresponding to fuel, product, desolation and exergy efficiency and exergy destruction ratio of the units of the MHD system (up to APH, the values are based on initial data of Haloi and Gogoi [32]). MHD System unit j πœ“ ̇𝐹,𝑗 (π‘€π‘Š) πœ“ ̇𝑃,𝑗 (π‘€π‘Š) πœ“ ̇𝐷,𝑗 (π‘€π‘Š) πœ€ 𝑗 (%) 𝛾 The results of the present study are verified with the work presented in [46]. For the purpose of validation, the combustion chamber and the MHD generator, having air and fuel input and the power output in Ref.…”
Section: Resultssupporting
confidence: 78%
“…Exergy rates corresponding to fuel, product, desolation and exergy efficiency and exergy destruction ratio of the units of the MHD system (up to APH, the values are based on initial data of Haloi and Gogoi [32]). MHD System unit j πœ“ ̇𝐹,𝑗 (π‘€π‘Š) πœ“ ̇𝑃,𝑗 (π‘€π‘Š) πœ“ ̇𝐷,𝑗 (π‘€π‘Š) πœ€ 𝑗 (%) 𝛾 The results of the present study are verified with the work presented in [46]. For the purpose of validation, the combustion chamber and the MHD generator, having air and fuel input and the power output in Ref.…”
Section: Resultssupporting
confidence: 78%
“…The results express that the storage tank has the most exergy destruction rate and the highest cost of exergy destruction rate. Esmaeilzadehazimi et al [21] analyzed an MHD-Magneto hydrodynamic-cycle from 4E points of view. In MHD cycles, the waste heat can be recovered and used in the Brayton cycle as a heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Esmaeilzadehazimi has been disclosed a 4E analysis of integrated magnetohydrodynamic (MHD) combined cycle. The authors have been reported that the cost of exergy destruction decreased, and the efficiency increased in their proposed cycle [23].…”
Section: Introductionmentioning
confidence: 99%